TATA KELOLA FESTIVAL WARGA: MENATA RANGKA KERJA KOLEKTIF - Dedi Novaldi; Dede Pramayoza (Melayu Arts and Performance Journal, 2022)
This article presents the results of research on various Festival Warga management in several places in Indonesia. Festival Warga is a concept that is growing and developing today as part of the cultural literacy movement, as part of the ideals of sustainable cultural development. The purpose of research is to describe and analyze the development model of the Festival Warga, as a reference for the development of community-based festivals, with an emphasis on the development of the Festival Warga ecosystem. The research was conducted qualitatively, with primary data from involved observations and literature studies. The results of the research are presented in a descriptive analysis method, containing an offer of concepts and basic principles of developing Festival Warga. The results of the study indicate that there are three basic principles in the development of the Festival Warga: (1) Sense of Ownership and Involvement in the Festival; (2) Principles of Cadre in the Development of Production Teams; and (3) the Mutual Cooperation Pattern as an Indicator of Implementation Success.Keywords: management; festival warga; a sense of ownership; cultural ecosystem; mutual cooperation AbstrakArtikel ini menyajikan hasil penelitian tentang berbagai Tata Kelola Festival Warga di beberapa tempat di Indonesia. Festival Warga adalah sebuah konsep yang tumbuh dan berkembang dewasa ini sebagai bagian dari gerakan literasi budaya, sebagai bagian cita-cita pembangunan kebudayaan berkelanjutan. Tujuan penelitian adalah untuk mendeskripsikan dan menganalisis model pengembangan Tata Kelola Festival Warga, sebagai referensi bagi pembangunan festival berbasis masyarakat, dengan empasis pada pembangunan ekosistem festival warga. Penelitian dilakukan secara kualitatif, dengan data primer hasil observasi terlibat dan studi pustaka. Hasil penelitian disajikan dengan metode analisis deskriptif, memuat tawaran konsep dan prinsip-prinsip dasar pengembangan festival warga di Nusantara. Hasil penelitian menunjukkan bahwa terdapat tiga prisip dasar dalam pembangunan Festival Warga, yakni: (1) Rasa Kepemilikan dan Keterlibatan dalam Festival; (2) Prinsip Pengkaderan dalam Pembangunan Tim Produksi; dan (3) Pola Gotong Royong sebagai Indikator Keberhasilan Pelaksanaan.Kata Kunci: tata kelola; festival warga; rasa kepemilikan; ekosistem budaya; gotong royong